COLOURED FRUITS AND VEGETABLES FOR HEALTHY BODY - Khatri, Amrita (International Journal of Research -GRANTHAALAYAH, 2014)
Fruits and vegetables are extremely essential to our healthiness because they are whole foods, produced by natural world. They are rich in a large amount of nutrients, as they possess fiber, vitamins, and enzymes .Each different color fruit and vegetable contains unique health components that are essential to our health. Green color is very crucial in diet. Green vegetables contain chlorophyll, calcium, folate, vitamin C, calcium, and beta-carotene. The green fruit and vegetables are also rich in phytochemicals which are important in keeping the healthy body e.g. spinach has carotinoids, lutein and zeaxanthin .The antioxidant properties possessed by broccoli are good to defend the eyes by keeping the retina healthy and powerful. Peas and lima beans are also good sources .The green Fruits and vegetables are also encumbered with necessary minerals and fibers. The green vegetables are loaded with cancer blocking chemicals like sulforaphanes, isosynate and indols which reduces the stroke of carcinogens. They are also associated with reduction of cataract and age related muscular degeneration, thus also controls blindness. The nutrients found in these vegetables reduce cancer risks, lower blood pressure, LDL cholesterol levels, normalize digestion time, support retinal health and vision, fight harmful free-radicals, and boost immune system activity. Green colour of fruits and vegetables enhances calcium absorption, boosts mental alertness and helps in cell regulation.